Global Violence: Some Thoughts on Hope and Change - McPhillips, Kathleen (Feminist theology, 2005)
In these early years of the new millennium the world finds itself in a new age of violence and terror. Acts of terrorism, the war in Iraq, and the ongoing post-colonial struggles have created a climate of unprecedented state legitimated and terrorist-based violence, where the emergence of new forms of national insecurity and vulnerability have impacted on every nation and distant corner of the plane. One looks at the world situation and despairs: it is almost impossible to feel safe in the face of such unpredictability. Patriarchy in its various guises (state power, terrorism, war, hate), intent on domination and destruction, seems all encompassing and powerful. The questions we ask are enormous: how do we respond and what can we do? Where will genuine moral leadership come from? Where are the signs of hope—true hope—hope born from realism not romanticism? And in particular, as feminists and religionists and theologians, what should our particular contribution be? It is more important than ever to understand hope, and how it generates change. I believe that there are two aspects to global violence that we as feminist religionists and theologians need to tackle in particular. The first is to continue to offer analysis around understanding what hope is, where it derives from, and how it can be transformed into action and motivation. Second, we are experts in two of the principal characteristics of the current global power arrangements—gender and religion—so we have a special responsibility to provide analysis and visionary thinking to our communities. I would like to suggest that the particular contributions that we can make could be firmly placed in the realm of an emerging feminist religious imaginary, because this is the site where our political action and ideas are sustained, nurtured, challenged and where hope is born via imaginative and visionary thinking, where biophillic rationalities and responses are possible. This paper reads global violence and locates hope within a feminist religious imaginary.